The crisis of normality in the capitalist socio-economic context - Guajardo Romero, Angel V. (2021)
Inaction has allowed unprecedented reflection, especially in peripheral countries, where inequalities inherent to the socioeconomic system have accelerated and exacerbated with the current health crisis. The critical analysis of normality, allows the discussion about the values that have allowed the reproduction of phenomena harmful to life. For many authors, this is a time when the political possibility opens up, to dispute future development trends. The new normality is presented as a possibility imposed from above or as one built from the grassroots where the key is the creation of a new conceptual framework, consistent with the current political responsibility, which provides social movements, with the theoretical support for their renewal and for the creation of new strategies. that allow a basic democratic response to the tendencies of repression and state violence.